Guinness world records 2020 - Guinness World Records Limited ([London, England] Guinness World Records Limited, 2019)
"The world's most popular record book is back with thousands of new categories and newly broken records, covering everything from outer space to sporting greats via Instagram, fidget spinners and all manner of human marvels. Inside you'll find hundreds of never-before-seen photographs and countless facts, figures, stats and trivia waiting for you on every action-packed page. Guinness World Records 2019 is the ultimate snapshot of our world today."--Publisher's description
Encyclopedias
2
Keywords: Curiosities and wonders; World records